One + one : scarves, shawls & shrugs : 25+ projects from just two skeins - Schreier, Iris (Lark Crafts, 2012)
Presents detailed instructions for twenty-five projects for creating a variety of shawls, scarves, cowls, and capes, with advice on techniques and finishing details.